ANALYSIS OF THE IMPLEMENTATION OF THE MERDEKA CURRICULUM AND THE TYPICAL AL-FALAH FOUNDATION CURRICULUM: CONSTRAINTS AND OPPORTUNITIES - ASYZUMAR, HAIDAR IZZAD; NOVITASARI, VERISKA DHEA; WULANSARI, DIAH AYU; NAFI’AN, FAJAR ILMAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
An independent curriculum is a curriculum that gives schools and teachers the freedom to adapt the learning process to the potential needs of students. This curriculum emphasizes flexible learning, focuses on developing students' character, creativity and basic competencies and encourages students to be more contextual and independent regarding the issues they face. Meanwhile, the Al-Falah Foundation implements a unique curriculum that is adapted to the religious values ??and local characteristics of the foundation. This research aims to analyze the implementation of the independent curriculum and the typical Al-Falah foundation curriculum, focusing on the obstacles and opportunities that arise in its implementation. The approach to this research uses a qualitative approach. Data analysis for this research uses descriptive analysis, data obtained from in-depth interviews, observation and documentation. In this analysis, the data is interpreted descriptively and expressed narratively. The results of the research show opportunities such as flexibility in developing teaching materials so that it makes it easier to adapt the foundation's curriculum to the independent curriculum, giving foundations the freedom to determine learning models and policy models that suit the characteristics of the foundation, as well as there is room for integration of local values ??with national education standards. Several obstacles include teachers' lack of understanding regarding the independent curriculum, limited facilities and infrastructure, limited time for integration with the local foundation curriculum, resistance to change. ABSTRAKKurikulum mandiri merupakan kurikulum yang memberikan kebebasan kepada sekolah dan guru untuk menyesuaikan proses pembelajaran dengan potensi kebutuhan siswa. Kurikulum ini menekankan pembelajaran yang fleksibel, berfokus pada pengembangan karakter, kreativitas, dan kompetensi dasar siswa serta mendorong siswa untuk lebih kontekstual dan mandiri terhadap permasalahan yang dihadapinya. Sedangkan Yayasan Al-Falah menerapkan kurikulum unik yang disesuaikan dengan nilai-nilai agama dan karakteristik lokal yayasan. Penelitian ini bertujuan untuk menganalisis implementasi kurikulum mandiri dan kurikulum khas yayasan Al-Falah, dengan fokus pada hambatan dan peluang yang muncul dalam implementasinya. Pendekatan penelitian ini menggunakan pendekatan kualitatif. Analisis data pada penelitian ini menggunakan analisis deskriptif, data diperoleh dari wawancara mendalam, observasi dan dokumentasi. Dalam analisis ini, data ditafsirkan secara deskriptif dan diungkapkan secara naratif. Hasil penelitian menunjukkan adanya peluang seperti fleksibilitas dalam mengembangkan bahan ajar sehingga memudahkan penyesuaian kurikulum yayasan dengan kurikulum mandiri, memberikan kebebasan kepada yayasan untuk menentukan model pembelajaran dan model kebijakan yang sesuai dengan karakteristik yayasan, serta serta masih adanya ruang integrasi nilai-nilai lokal dengan standar pendidikan nasional. Beberapa kendala yang dihadapi antara lain kurangnya pemahaman guru mengenai kurikulum mandiri, keterbatasan sarana dan prasarana, terbatasnya waktu integrasi dengan kurikulum yayasan lokal, dan penolakan terhadap perubahan.